Enzymatic Synthesis, Characterization and Analytical Applications of Fatty Hydrazides from Palm Oil - Mohamad, Sharifah (2008)
Hydrazides with the general formula R-CO-NHNH2, have received a lot of attention due to their applications in biological, organic synthesis and analytical chemistry fields. The preparation of fatty hydrazides from palm oil has been developed in this research. Fatty hydrazides (FH) and fatty phenyl hydrazides (FPH) were successfully synthesized from palm oil as a raw material by one-step lipase catalyzed reaction. FTIR and CHN elemental analyses were carried out to determine the presence of the hydrazides in the products. The method offers several advantages such as renewable and abundant of raw materials, simple reaction procedure and high yield of products. The application of the products as a reagent was carried out based on the ability of the FH and FPH to form complexes with some metal ions. FH was successfully used as an extractant for extraction and separation of copper(II). The separation of Cu(II) is possible from other metal ions such as Co(II), Cr(VI), Ni(II), Zn(II) and Fe(III) at pH 5.5-6.5. A preconcentration method was proposed for the determination of Cu(II) in water samples. It was shown that the extraction from aqueous phase containing Cu(II) with organic phase containing FH and then stripping the organic phase with 2 M of HCl solution give a solution of Cu(II) 10 fold in concentrations. FH was also successfully used as an extractant for extraction and separation of Mo(VI). This metal successfully separated from other metal ions such as Ni(II), Co(II), Al(III), Fe(III) and Mn(II). Quantitative stripping of Mo(VI) ion from the organic phase can be carried out using 2 M ammonium hydroxide. This proposed method was applied for the recovery of Mo(VI) from synthetic mixture and the results showed that more than 90% recovery of Mo(VI) is achieved and the metal ion solution is free from the impurities. FH and FPH were also evaluated as an extractant for extraction and separation of gold(III) from chloride media. This metal was extracted quantitatively from hydrochloric media at 0.001-0.1 M into the organic phase. Gold(III) was successfully separated from Cu(II), Ni(II), Zn(II), Co(II) and Fe(III) by using FH or FPH. Quantitative stripping of gold(III) from the organic phase can be carried out using 2.0 M thiourea in 1.0 M HCl solution. The extraction and separation of gold(III) by FH or FPH was applied to separate and recover pure gold(III) from synthetic mixtures. FPH synthesized from palm olein was also successfully used as a new reagent for the determination of V(V) by spetrophotometric method. The method is based on the colored complex of vanadium(V)-FPH. The metal ion forms dark brown colored complex which has an absorption maximum at 405 nm. Beer’s law is valid over the concentration range of 0.2-20 mg/L and the limit of detection of this method is 0.01 mg/L. The characteristics of this developed method are simple, good selectivity, high sensitivity and rapid.